O animal enfermo: pessimismo antropológico e a possibilidade gnóstica na obra de Emil Cioran - Menezes, Rodrigo Inácio Ribeiro Sá (2007)
Focusing on the works of the Rumanian philosopher Emil Cioran (1911-1995), this study proposes an anthropological approach in order to elucidate the author s conception regarding human being. Cioran s writings portrait man as an essentially infirm being, idea from which this study takes off so as to explain what lies behind his anthropological pessimism. For such, it takes gathering, analyzing and interpreting the reflections offered by him on human being his origins, condition, history and destiny and that are spread out throughout his books. Besides, some of his critics will contribute to sustain the hypothesis: more than just a philosopher, Cioran is a religious thinker, whose pessimistic conception regarding human condition is rooted in gnostic soil. As it is intended to be demonstrated, his connections with gnosticism go way beyond a mere intellectual affinity, involving as well a kinship with the bogomils, a gnostic sect which settled in the Balkans during the Middle Ages and which is supposed to have had a significant role in shaping Rumania s cultural identity. Furthermore, it intends to argue that the crisis of insomnia endured by Cioran in his youth period has a cognitive and spiritual character allowing her to be interpreted as a gnosis. At last, this study commits itself with sustaining the following thesis: much more than his readings, it is rather his insomniac experience that turns out to be the decisive event responsible to shape his thought from then on, including his world and man view